2016
DOI: 10.1371/journal.pone.0146569
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Overexpression of MEOX2 and TWIST1 is Associated with H3K27me3 Levels and Determines Lung Cancer Chemoresistance and Prognosis

Abstract: In Fig 4, the statistical significance indicators are missing. Please see the corrected Fig 4 here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…A recent study showed that ERMN was connected to the Wnt pathway and might be a candidate gene that drives hepatoblastoma 45 . Mesenchyme Homeobox 2 (MEOX2) is related to the malignant progression of various tumors 38 , 46 , but its specific role in colorectal cancer has not been studied. A study suggests that MEOX2 may play a role in the carcinogenic process of colon adenocarcinoma 47 , but the specific mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that ERMN was connected to the Wnt pathway and might be a candidate gene that drives hepatoblastoma 45 . Mesenchyme Homeobox 2 (MEOX2) is related to the malignant progression of various tumors 38 , 46 , but its specific role in colorectal cancer has not been studied. A study suggests that MEOX2 may play a role in the carcinogenic process of colon adenocarcinoma 47 , but the specific mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that ERMN was connected to the Wnt pathway and might be a candidate gene that drives hepatoblastoma. 44 Mesenchyme Homeobox 2 (MEOX2) is related to the malignant progression of various tumors 37,45 , but its specific role in colorectal cancer has not been studied. A study suggests that MEOX2 may play a role in the carcinogenic process of colon adenocarcinoma 46 , but the specific mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…TWIST1 was additionally a target in lung cancer, which was correlated with the inhibition of proliferation, epithelial-mesenchymal transition and metastasis ( 51 ). Furthermore, overexpression of TWIST1 was additionally identified to determine lung cancer chemoresistance and prognosis ( 52 ). TWIST1 was additionally documented to be associated with the invasion and metastasis of gastric cancer ( 53 , 54 ), and was a potential prognostic marker in colorectal cancer ( 55 57 ).…”
Section: Discussionmentioning
confidence: 99%